Gene Expression of Human Mesenchymal Stem Cells Cultured on Titanium Dental Implant Surfaces. Issue 3 (May 2016) - Barone, Antonio; Toti, Paolo; Bertossi, Dario; Marconcini, Simone; De Santis, Daniele; Nocini, Pier Francesco; Iurlaro, Antonio; Alfonsi, Fortunato; Covani, Ugo
Abstract : Objective: The study shows how the influence of titanium surfaces on human mesenchymal stem cells differentiates toward osteocytes lineage and how, after growth, on machined titanium disk or etched titanium disk, changes, in gene expression for RUNX1, CTNNB1, SP7, and DLX5. Methods: Genes were analyzed by means of quantitative real-time polimerase chain reaction. Osseo genic lineage differentiation was also tested by means of the catenin-β1 immunofluorescence, induced osteoblasts, which represented the internal control. Results: The RUNX1 and SP7 expressions in the induced osteoblasts prove to be different, compared with cells cultured on metallic supports. Moreover, the levels of expression of the runt-related transcription factor 1 and the osterix appeared more down-regulated in cells that grew on a machined titanium surface. In the present experimental model, mRNA expression of DLX5 and CTNNB1 in human mesenchymal stem cells, cultured on each of the titanium surfaces, showed no differences, compared with osteoblast-induced cells. The immunofluorescence scores, for protein expression of beta-catenin in human mesenchymal stem cell treated cells, illustrates significantly improved results with the etched surface. Conclusions: Present results suggested that different titanium surfaces might induce some differences in terms of gene expression. The only gene analyzed, which proved significant differences between the 2 titanium supports, was SP7; however, the other 3 genes indicating the existence of differences between the 2 titanium groups.